The expanding role of the epicardium and epicardial-derived cells in cardiac development and disease - Ruiz-Villalba, Adrián; Pérez-Pomares, José María (My University, 2012)
In this review, we aim at presenting and discussing the cellular and molecular mechanisms of embryonic epicardial development that may underlie the origin of congenital heart disease (CHD).
Keywords: Corazón -- Enfermedades; Desarrollo cardiaco; Enfermedad congénita; Epicardio